Rhythmic models of technical actions of sportsmen karate-do of high qualification. - Mudryk Ivan Petrovich (Kharkov National Pedagogical University, 2011)
The rhythmic structure of attacking actions is considered in karate-do. Specificity of feeling of rhythm and his intercommunication is shown with technical and tactical by the aims of concrete actions. 12 highly skilled sportsmen took part in research (men in age 19-24). The rhythmic models of attacking are developed actions. Found out the sentinel intervals of basic phases of technical actions of sportsmen. It is recommended to carry out control after the level of development of feeling of rhythm for sportsmen on the sentinel intervals of basic phases.